Numerical simulation of laser energy discharge for flight control. (24th September 2019) - Kianvashrad, Nadia; Knight, Doyle
Abstract: The numerical investigation of the interaction of an off-axis laser discharge in front of an ogive cylinder at Mach 3.4 is presented. Details of the physics of the interaction of the blast wave and heated region with the ogive cylinder shock structure and the effect of this interaction on the drag, side force and pitching moment are included. The location of laser discharge and the amount of energy added to the gas by the laser are two main factors affecting the flow. Increasing the energy absorbed by the gas increases the drag reduction, the desired side force and pitching moment. Increasing the distance of the discharge from the axis reduces both drag reduction and side force achieved by the laser discharge.